Knowledge on gastric cancer, attitude on screening for gastric cancer and screening behavior of gastric cancer among out patients in Hospital Universiti Sains Malaysia - Saffai, Siti Norzietai (Universiti Sains Malaysia, 2023)
Gastric cancer is heterogenous or multifactorial disease which is it affects the human physical and psychosocial well-being and leading cause of morbidity, mortality, economic burden in both developed and developing countries. This study aims to determine the knowledge, attitude of screening, screening behaviour of gastric cancer and factors associated with knowledge and screening behaviour among out patients in Hospital Universiti Sains Malaysia. A cross-sectional survey was carried out using a set of self-administered questionnaires. This study was used convenient sampling method and the total sample size was 219 samples which taken from objective 2. The questionnaire used in this study was adapted and adopted from (Liu et al., 2019; Huang et al., 2022). The data was analysed using SPSS version 26. Most of the respondent showed that had poor knowledge of gastric cancer and majority of respondent had a good attitude towards screening for gastric cancer. The gender and educational level had significant association with knowledge (p<0.05). In conclusion, most out-patient in HUSM had lack of knowledge regarding gastric cancer. Hence, there is need for more education, awareness on screening for gastric cancer.